2012
DOI: 10.1111/cts.12005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Propranolol as Antiadhesive Therapy in Sickle Cell Disease

Abstract: Sickle red blood cells (SSRBCs) adhere to both endothelial cells (ECs) and the extracellular matrix. Epinephrine elevates cAMP in SSRBCs and increases adhesion of SSRBCs to ECs in a β adrenergic receptor and protein kinase A-dependent manner. Studies in vitro as well as in vivo have suggested that adrenergic stimuli like epinephrine may contribute to vaso-occlusion associated with physiologic stress. We conducted both animal studies and a Phase I dose-escalation study in sickle cell disease (SCD) patients to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 26 publications
0
33
0
Order By: Relevance
“…148 Beta-adrenergic receptor blockade, which targets epinephrine-mediated red cell adhesion, 95,149-152 has been used in patients, using an U.S. Food and Drug Administration (FDA) approved medication (propranolol). 153 Red cell adhesion to an activated endothelium has specifically been targeted with small molecules ( α V β 3 ), 154 low-molecular-weight heparin (P-Selectin), 155,156 and an oral agent in phase I/II studies in humans (P-selectin). 125,157,158 Abnormal interactions between leukocytes and activated endothelium and endothelial selectins have been targeted in vitro and in vivo with antibodies and small molecules 159-162 and are now the focus of phase II and III clinical studies in SCD.…”
Section: Discussionmentioning
confidence: 99%
“…148 Beta-adrenergic receptor blockade, which targets epinephrine-mediated red cell adhesion, 95,149-152 has been used in patients, using an U.S. Food and Drug Administration (FDA) approved medication (propranolol). 153 Red cell adhesion to an activated endothelium has specifically been targeted with small molecules ( α V β 3 ), 154 low-molecular-weight heparin (P-Selectin), 155,156 and an oral agent in phase I/II studies in humans (P-selectin). 125,157,158 Abnormal interactions between leukocytes and activated endothelium and endothelial selectins have been targeted in vitro and in vivo with antibodies and small molecules 159-162 and are now the focus of phase II and III clinical studies in SCD.…”
Section: Discussionmentioning
confidence: 99%
“…Propranolol was administered to SCD patients in a phase 1 dose escalation study and significantly reduced epinephrinestimulated SS-RBC adhesion in a dose-dependent manner. 38 Adverse events were not severe, did not show dose dependence, and were likely unrelated to drug. These results imply that b-blockers have a potential role as antiadhesive therapy via inhibition of cAMP-mediated inhibition of SS-RBC adhesion, which did not always correlate with areas of leukocyte adhesion.…”
Section: Targeting Adhesionmentioning
confidence: 94%
“…Adverse events were not severe, did not vary with the dose administered and no elevation in heart rate was noted. These results imply that β-blockers have a potential role in inhibiting RBC adhesion [61]. A phase 2 study of propranolol in SCD has been completed and no data has been reported at the time that this manuscript was written (NCT 01077921).…”
Section: Targeting Adhesionmentioning
confidence: 99%